The development of civic identity with junior schoolchildren as a key aspect of patriotism: analysis of Russian folk art potential - E. L. Voishcheva (Вестник Северо-Кавказского федерального университета)
Introduction. The issue of forming the civic identity of younger schoolchildren is one of the key aspects of the development of patriotism among the younger generation. The article draws attention to the fact that primary school children are inthe process of forming their personality and self-consciousness and it is in this period that it is especially important to moderate the process of forming their civic identity.Goal. The article studies the potential of Russian folk art in terms of patriotic education of junior schoolchildren, specifically the formation of their civic identity.Materials and methods. The research is carried out on the basis of analysis and generalisation of modern scientific works in the sphere of patriotic education. A complex of diagnostic methods is implemented. They allow diagnosing the multicomponent structure of children’s civic identity; various methods of studying Russian folk art from the point of view of forming junior schoolchildren’s civic identity are used.Results and discussion. The study presents the data of experimental work, proving that folk art is a powerful tool in the formation of civic identity of junior schoolchildren, helping them to realize that they belong to the Russian culture and nation, developing their emotional sphere and engendering patriotic feelings in their souls. The author has developed and described a systematic mode of work in primary school with various genres of folk art: songs, fairy tales, epic ballades (bylinas), proverbs, and ditties, allowing children to immerse themselves in the culture of their country, to study and become imbued with national traditions and values of the Russian people.Conclusion. The author proves that it is very important for a teacher to use folk art in the educational process and to create conditions for its active mastering by children, which will help to form civic identity with junior schoolchildren and make a significant contribution to the development of patriotism in Russian society in general.